ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI WAKTU KERJA DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA NELAYAN (Kasus Nelayan Malabero Kecamatan Teluk Segara Kota Bengkulu) - Nurung, Muhammad; Romdhon, Mustopa; Mandrik, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
Oceanic sector development basically represent an process to alter potency exist in sea region become an worthwhile to society. In general, fisherman in Bengkulu province is traditional fisherman owning simple equipments, capital a few and way of simple production. Fisherman also face the condition of less beneficial environment like situation waving sea enough strength, weather, and dicey climate, so that influence arrest time allocation. Thereby, fisherman look for alternative work utilize to fulfill requirements of his family.Research targets is knowing factors influencing in working allocation at the fishery catch sector and the outside, knowing how big contribution of the fisherman allocation work, knowing how big contribution of the fisherman time work at the fishery catch sector and the outside toward totalize in working, and knowing how big contribution of the fisherman earnings in working at the fishery catch sector and outside toward totalize earnings.The research location in Sub-District of Malabero District of Teluk Segara at Bengkulu City. Key words: contribution, time work, fisherman